Real-world comparative effectiveness and safety of rivaroxaban and warfarin in nonvalvular atrial fibrillation patients. (July 2014) - Laliberté, François; Cloutier, Michel; Nelson, Winnie W.; Coleman, Craig I.; Pilon, Dominic; Olson, William H.; Damaraju, C.V.; Schein, Jeffrey R.; Lefebvre, Patrick
Abstract Background: Rivaroxaban was shown to be effective in reducing the risk of stroke and systemic embolism in patients with nonvalvular atrial fibrillation (AF) in a randomized controlled trial setting. Objective: To assess real-world safety, effectiveness, and persistence associated with rivaroxaban and warfarin in nonvalvular AF patients. Methods: Healthcare claims from Symphony Health Solutions' Patient Transactional Datasets from May 2011 to July 2012 were analyzed. Adult patients newly initiated on rivaroxaban or warfarin, with ≥2 AF diagnoses (ICD-9-CM: 427.31) and a CHADS2 score ≥1 during the 180 day baseline period were included. Cohorts were matched 1:4 using propensity score methods. Study outcomes were major bleeding, intracranial hemorrhage (ICH), gastrointestinal (GI) bleeding, composite stroke and systemic embolism, and venous thromboembolism (VTE) events. Cox proportional hazard models were used to compare event and persistence rates. Results: The matched sample included 3654 rivaroxaban and 14, 616 warfarin patients. Matching was adequate, with all standardized differences in patient characteristics <10%. No significant differences were observed for bleeding and composite stroke and systemic embolism outcomes, although rivaroxaban users were associated with significantly fewer VTE events (hazard ratio [HR] = 0.36, 95% confidence interval [CI]: 0.24–0.54, p < 0.0001) compared to warfarin users. Rivaroxaban was also associated with a significantly lower risk of treatment non-persistence (HR = 0.66; 95% CI: 0.60–0.72, p < 0.0001). Limitations: Claims data may have contained inaccuracies, and mortality and laboratory data were not available. Confounding may still have been possible even after propensity score matching. Early use pattern of medications may have changed over time. Conclusion: This analysis suggests that rivaroxaban and warfarin do not differ significantly in real-world rates of composite stroke and systemic embolism and major, intracranial, or GI bleeding. Rivaroxaban, however, was associated with significantly fewer VTE events and significantly better treatment persistence compared with warfarin.